Perancangan Web Design Sebagai Marketplace Online Brand “Hanif” (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2024)
In the growing of digital era, technological advances have brought many innovations in the use of websites as a marketplace online for online sales and promotions. The use of the website is by designing a web design. Good web design includes not only visual aesthetic aspects, but also functionality, intuitive navigation, and responsiveness to various devices and users. Due to advances in technology and utilizing it, methods of disseminating information can be very easy and fast to do. Through a qualitative approach and design studies that can explore various aspects of design, including illustration and UI/UX which influence visual value and function.